Selected Information Source Perceptions and Use Patterns in One Rural Ohio County - an Analysis - Ted L. Napier; Peggy J. Ross; Douglas Bachtel (Journal of Applied Communications, 1976)
The major purpose of this paper is to present findings from a survey which was designed to evaluate information use patterns and perceptions of selected residents of a predominately rural county toward several mass media sources.